Practical Legal Issues of the Application of the Principle of Non-Interference in the Internal Affairs of States by Subjects of International Law (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
In this article, the concept of the principle of non-interference in the internal affairs of states by the subjects of international law, practical legal issues of the application of the principle of non-interference, the implementation of the UN Charter, the powers of the Security Council, the causes and consequences of the war between Russia and Ukraine, addressing regional organizations in peacekeeping operations procedure will be explained.